The impact of UK Law on sport - Crainey, S.; Codona, R.; Elder, B. (2020)
Sport is often viewed as a special entity whereby the law and legal systems do not directly interfere with its rules (Laver, 2020). Therefore, the rules under which a particular sport is played are not an area where the legal system will usually interfere.